2018
DOI: 10.1111/jog.13790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of sexual function in midlife partnered Chinese women assessed by two simple indicators: Sexual frequency and sexual desire

Abstract: Aim: To investigate the prevalence and predictors of sexual frequency, sexual desire in midlife partnered Chinese women. Methods: Sexual frequency, sexual desire over the past 3 months, menopausal symptoms and other socioeconomic information were assessed for women aged 40-65 years in the Shanghai Sixth People's Hospital. Results: Among 3485 eligible partnered participants, the prevalence of low sexual frequency (less than once per week) and low sexual desire (less than 5 scores) were 72.74% (95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
8
1
Order By: Relevance
“…Based on the survey results, low sexual desire was observed in middle-aged and old Chinese women (58%). However, the prevalence of sexual desire and activity was lower than that reported in a previous study on Chinese women of a similar age group (72.74%) [26]. Moreover, Zhou et al reported that sexual desire and activity decreased the most among postmenopausal women compared with peri-or premenopausal women [26].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Based on the survey results, low sexual desire was observed in middle-aged and old Chinese women (58%). However, the prevalence of sexual desire and activity was lower than that reported in a previous study on Chinese women of a similar age group (72.74%) [26]. Moreover, Zhou et al reported that sexual desire and activity decreased the most among postmenopausal women compared with peri-or premenopausal women [26].…”
Section: Discussionmentioning
confidence: 55%
“…However, discussing sexual health, especially FSD or sexual activity, is still a taboo in Asian countries [15,36]. As China is also a conservative country where research on sexual health, reproductive health, contraceptive use, and menopause-related problems has been limited [23], FSD or sexual health has been inadequately studied [25,26]. Other studies in Hong Kong and China have also reported the prevalence and risk factors of FSD in young and middle-aged women [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual function is an important dimension of life and has significant effects on the emotional and physical health of an individual (1,2). Female sexual dysfunction can be affected by a number of biological, psychological, social, and medical factors, the identification of which helps in understanding the multidimensional nature of human sexuality (3). For instance, menstruation as an important symbol of sexual maturity and fertility potential of women had important effects on the different aspects of women's functioning (4,5).…”
Section: Introductionmentioning
confidence: 99%